Sistem Informasi Penerbitan Buku Menggunakan Model Waterfall Dalam SDLC - Jihan Maisyaroh (ADA Journal of Information System Research, 2024)
PT. Penerbit Mitra Group is one of the companies engaged in the field of book publishing. In the input of book publishing data is still manual and there is no support system in terms of making book publishing reports are still done manually, namely by inputting data one by one using the Microsoft Office Excel application, this causes a waste of time in making publishing reports. Therefore, a book publishing information system based on visual basic is needed to make it easier for employees to make book publishing reports so that they can save time in making the report. The system design stage used includes data flow diagrams (DFD), flowcharts and for data storage using MySQL databases and applications and the interface design is made as similar as possible to the old system so that it is easier for employees to adapt to the new system. The system that is built is expected to be able to help and ease activities in the company and can save time in making publishing data reports and produce final reports that are more accurate and easy to understand and comprehend.